The expression of glycosaminoglycans and proteoglycans in the uterine cervix of albino rats after local hyaluronidase infusion. (June 2014) - Souza, Guilherme Negrão; Camano, Luiz; Araujo Júnior, Edward; Nader, Helena Bonciani; Medeiros, Valquíria; Martins, João Roberto Maciel; Souza, Eduardo
Abstract Objective: To assess the local effect of hyaluronidase injection on the expression of glycosaminoglycans (GAGs) and proteoglycans (PGs) in the extracellular matrix of the uterine cervix from pregnant albino rats. Methods: Ten pregnant rats were divided into two groups on day 18 of pregnancy. The experimental group (Gexp) of rats received an intracervical infusion of 0.02 mL of hyaluronidase diluted to 1 mL with distilled water, whereas the control group (Gc) received 1 mL of distilled water. On day 20 of pregnancy, the pregnant rats were sacrificed and the uterine cervixes from all rats were then dissected. The qualitative expression of hyaluronic acid (HA) was assessed by immunohistochemistry and quantified by sandwich ELISA. To compare the quantitative GAG values between groups, a Student's t-test for independent samples was performed. PGs were also assessed by immunohistochemical analysis. Results: The electrophoretic profile of newly synthesized radioactively labeled GAGs degraded by specific enzymes showed that there were two predominant GAGs in both Gc and Gexp, i.e. heparan sulfate (HS) and a mixture of hondroitin sulfate (CS) and dermatan sulfate (DS). The concentrations of GAGs showed a significant reduction of CS/DS (p < 0.004) and HS (p < 0.005) relative to Gc. HA staining was less intense in the lamina propria and area surrounding the blood vessels in Gexp compared to Gc. The HA contents were also significantly reduced (p < 0.012). Conclusions: Intracervical hyaluronidase infusion promoted a significant reduction in the concentration of sulfated GAGs as assessed by both qualitative (histochemical) and quantitative (fluorometric) measurements of HA.